1993
DOI: 10.1016/0014-5793(93)81741-h
|View full text |Cite
|
Sign up to set email alerts
|

Early induction of Na+‐dependent uridine uptake in the regenerating rat liver

Abstract: Na+‐dependent uridine transport into liver plasma membrane vesicles from partially hepatectomized and sham‐operated rats was studied. Preparations purified 6 h after 70% hepatectomy exhibited an increased V max of uridine uptake (3.7 vs. 1.4 pmol/mg prot/3 s) without any change in Km (6μM). Incubation of the vesicles in the presence of monensin decreased uridine uptake although the differences between both experimental groups remained identical. It is concluded that uridine transport is induced early after par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
(18 reference statements)
4
25
0
Order By: Relevance
“…The ultimate physiological role of this response requires further analysis, although a possible relationship between cell growth and up-regulation of concentrative nucleoside transporters has recently been shown in other cell types (19,46,47). These actions appear to be dependent on protein kinase C activation, which is consistent with previous reports based on HL-60 cells induced to differentiate (20 -22).…”
Section: Tnf-␣ Modulation and Role Of Pkc In The Regulation Of Nucleosupporting
confidence: 87%
“…The ultimate physiological role of this response requires further analysis, although a possible relationship between cell growth and up-regulation of concentrative nucleoside transporters has recently been shown in other cell types (19,46,47). These actions appear to be dependent on protein kinase C activation, which is consistent with previous reports based on HL-60 cells induced to differentiate (20 -22).…”
Section: Tnf-␣ Modulation and Role Of Pkc In The Regulation Of Nucleosupporting
confidence: 87%
“…Indeed, the Na ϩ -dependent transport activity, which has been characterized in detail both in liver plasma membrane vesicles and in hepatocytes, [30][31][32]35,43 is significantly induced (nearly a threefold increase in V max ) in the prereplicative phase of liver growth after partial hepatectomy. 33 Moreover, pathophysiological conditions associated with liver hypertrophia, like genetic obesity, are also characterized by a selective induction of the Na ϩ -dependent transport activity for nucleoside uptake. 34 In agreement with these previous observations, in this report, it is shown that the SPNT mRNA levels increase as early as 2 hours after partial hepatectomy, just before the reported increase in the V max of the Na ϩ -dependent nucleoside transport activity.…”
Section: Discussionmentioning
confidence: 99%
“…34 In agreement with these previous observations, in this report, it is shown that the SPNT mRNA levels increase as early as 2 hours after partial hepatectomy, just before the reported increase in the V max of the Na ϩ -dependent nucleoside transport activity. 33 This effect can be reproduced in culture by synchronizing FAO cells and inducing them to proliferate by serum refeeding. Thus, when liver parenchymal cells are induced to proliferate, they selectively up-regulate this concentrative transport process, SPNT, by a mechanism that is consistent with de novo synthesis of nucleoside carriers, as also shown for other transport systems like those for neutral amino acids 44,45 and the Na,K-ATPase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies using monensin were performed as previously described [21] by incubating, simultaneously, the ionophore at a concentration of 20 PM and the substrate, r.-alanine, at 0.25 mM. Since dilution of the ionophore required 2% DMSO, uptake rates in its absence were measured in a DMSO-supplemented medium.…”
Section: ~Eai~-sensitive and Insensitive ~A~-dependent Lala~ine Uptakementioning
confidence: 99%